Integrating Financial Market Indicators and Macroeconomic Fundamentals in Explaining Exchange Rate Dynamics: Evidence from ASEAN Countries - Daniel Lutfi Izza Zudien; Muhammad Arif (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2026)
Purpose: This study aims to examine the effects of stock indices, trade balance, and economic growth on exchange rates in ASEAN countries.Method: This study adopts a quantitative approach using panel data from ten ASEAN member countries during the 2013–2022 period. The data were obtained from official publications of the World Bank and Investing.com. Panel data regression was employed as the analytical method. Based on the results of the Chow and Hausman tests, the Fixed Effects Model (FEM) was selected as the most appropriate model for estimating the relationships among the variables.Result: The results found that stock indices and trade balance have a positive effect on exchange rates. Meanwhile, economic growth has a negative effect on exchange rates in ASEAN countries.Practical Implications for Economic Growth and Development: The findings highlight the importance of maintaining financial market stability, improving international trade performance, and promoting sustainable economic growth to support exchange rate stability. These factors are essential for strengthening regional economic resilience in ASEAN.Originality/Value: This study incorporates financial market indicators and macroeconomic fundamentals within a cross-country panel data framework. By focusing on ASEAN countries during the 2013–2022 period, this study provides a more comprehensive understanding of the determinants of exchange rates in developing economies.